Thrombotic microangiopathies in critically ill children: The MATUCIP registry in Spain - Lorena Bermúdez Barrezueta; Sylvia Belda Hofheinz; Amelia Martínez De Azagra Garde; Sara Bobillo Pérez; Manuel Nieto Faza; Antonio Rodríguez Núñez (Elsevier, 2023)
Introduction: Thrombotic microangiopathies (TMA) are rare diseases usually presenting with renal, haematological, neurologic and cardiovascular involvement and nonspecific but severe symptoms. A registry of TMA cases managed in Spanish paediatric intensive care units (the MATUCIP Registry) was established with the aim of gaining knowledge on their clinical characteristics, diagnosis and acute-phase treatment. Methods: We conducted a prospective multicentre observational study in 20 paediatric intensive care units (PICUs) in Spain from January 2017 to December 2021 in children aged more than 1 month with TMAs, who were followed up through the discharge from the PICU. Results: The sample included 97 patients (51.5% female) with a median age of 2.6 years (interquartile range [IQR], 1.6-5.7). The initial manifestations were gastrointestinal (74.2%), respiratory (14.4%), fever (5.2%), neurologic (3.1%) and other (3.1%). At admission, 75.3% of patients had microangiopathic haemolytic anaemia, 95.9% thrombocytopenia and 94.8% acute kidney injury. Of the total sample, 57.7% of patients received a diagnosis of Shiga toxin-associated haemolytic uraemic syndrome (HUS), 14.4% of Streptococcus pneumoniae-associated HUS, 15.6% of atypical HUS, 10.3% of secondary TMA and 2.1% of thrombotic thrombocytopenic purpura. Eighty-seven patients (89.7%) developed arterial hypertension, and 49.5% gastrointestinal, 22.7% respiratory, 25.8% neurologic and 12.4% cardiac manifestations. Also, 60.8% required renal replacement therapy and 2.1% plasma exchange. Twenty patients received eculizumab. The median PICU stay was 8.5 days (IQR, 5-16.5). Two children died. Conclusions: The MATUCIP registry demonstrates the clinical variability of TMA cases requiring admission to the PICU. Knowledge of the presentation and outcomes of TMAs can facilitate early aetiological diagnosis. This registry can help improve our understanding of the clinical spectrum of these diseases, for which there is a dearth of published data. Resumen: Introducción: Las microangiopatías trombóticas (MAT) son entidades infrecuentes que suelen causar afectación renal, hematológica, neurológica y cardiovascular, con síntomas inespecíficos pero graves. Con la finalidad de mejorar el conocimiento de sus características clínicas, proceso diagnóstico y tratamiento en la fase aguda, se ha creado el registro de MAT en las Unidades de Cuidados Intensivos Pediátricos (UCIP) de España (Registro MATUCIP). Pacientes y métodos: Estudio observacional, multicéntrico realizado en 20 UCIP españolas desde enero 2017 hasta diciembre de 2021 que incluyó niños mayores de 1 mes con diagnóstico de MAT y seguimiento hasta el alta de UCIP. Resultados: Se incluyeron 97 pacientes (51,5% mujeres), con mediana de edad de 2,6 años (RIQ 1,6-5,7). La clínica inicial fue de tipo gastrointestinal (74,2%), respiratoria (14,4%), cuadro febril (5,2%), neurológica (3,1%) y otras (3,1%). Al ingreso, 75,3% presentaban anemia hemolítica microangiopática, 95,9% trombocitopenia y 94,8% daño renal agudo. Fueron diagnosticados de Síndrome Hemolítico Urémico (SHU) asociado a Escherichia coli productora de toxina Shiga 57,7%, SHU por Streptococcus pneumoniae 14,4%, SHU atípico 15,6%, MAT secundaria 10,3% y púrpura trombocitopénica trombótica 2,1%. Desarrollaron hipertensión arterial 89,7%, manifestaciones digestivas 49,5%, respiratorias 22,7%, neurológicas 25,8% y cardiacas 12,4%. El 60,8% requirieron depuración extrarrenal y 2,1% plasmaféresis. Recibieron eculizumab 20 pacientes. La mediana de estancia en UCIP fue 8,5 días (RIQ 5-16,5). Dos niños fallecieron. Conclusiones: El registro MATUCIP muestra la variabilidad clínica de las MAT que ingresan en UCIP. Conocer la forma de presentación y evolución de las MAT puede facilitar el diagnóstico etiológico precoz. Este registro permite conocer mejor el espectro clínico de estas entidades donde los datos publicados son escasos.